The Role of CD68 (+) Histiocytic Macrophages in Nasal Polyp Development - Bayar Muluk, Nuray; Arikan, Osman Kürşat; Atasoy, Pınar; Kiliç, Rahmi; Tuna Yalçinozan, Eda (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives The aim of this study was to investigate the role of CD68 (+) histiocytic macrophages (H-M) in the nasal polyp pathogenesis.Materials and Methods The study group consisted of 24 adult patients with nasal polyposis. The control group consisted of 11 adult patients without nasal polyps. A total of 36 nasal polyp samples (10-nasal cavity, 10-maxillary sinus, and 16-ethmoid sinus) from the study group and 11 inferior turbinate samples from the control group were analyzed by immunohistochemical staining, with monoclonal antibodies against CD68 (+) H-M.Results CD68 positivity was significantly higher than the control group in the subepithelial (SE) layer of the ethmoid sinus, and deep layers of nasal cavity, maxillary, and ethmoid sinuses. In SE and deep layers of ethmoid and maxillary sinuses, CD68 positivity was significantly higher than that of the epithelial layer. In the deep layer, histiocytic macrophages tended to gather around eosinophils.Conclusion The high numbers of CD68 (+) histiocytic macrophages mainly located in deep layer of lamina propria may be responsible for the phagocytosis of eosinophils within the polyp tissue. Therefore, it may be concluded that increased macrophages in nasal polyps do not trigger the growth of nasal polyps. Instead, they may serve to reduce the number of eosinophils in already-developed nasal polyps.
Keywords: CD68 (+); histiocytic macrophages; polyp; ethmoid sinus; maxillary sinus; nasal cavity; pathogenesis